A trifunctional mesoporous silica-based, highly active catalyst for one-pot, three-step cascade reactions1. Issue 40 (18th May 2015) - Biradar, Ankush V.; Patil, Vijayshinha S.; Chandra, Prakash; Doke, Dhananjay S.; Asefa, Tewodros
<x xml:space="preserve">Abstract</x> We report the synthesis of a trifunctional catalyst containing amine, sulphonic acid and Pd nanoparticle catalytic groups anchored on the pore walls of SBA-15. The catalyst efficiently catalyzes one-pot three-step cascade reactions.